2003
DOI: 10.1002/ajmg.b.20038
|View full text |Cite
|
Sign up to set email alerts
|

Influence of CLOCK gene polymorphism on circadian mood fluctuation and illness recurrence in bipolar depression

Abstract: Recent studies showed that a polymorphism (T to C nucleotide substitution) in the 3' flanking region of the human CLOCK gene is associated with diurnal preferences of human healthy subjects, with higher "eveningness" in subjects carrying at least one copy of the C allele. We investigated the possible role of CLOCK gene polymorphism in the regulation of diurnal mood fluctuations during a major depressive episode. Sample (n = 101) was collected, in the context of previously reported trials, among patients affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
151
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(165 citation statements)
references
References 19 publications
6
151
0
5
Order By: Relevance
“…17 Although we did not perform any assessment of sleep patterns in our subjects, it is of interest that the rs1801260 polymorphism has previously been associated with sleep dysregulation in humans in many [31][32][33][34][35][36][37][38] but not all studies. 39 These findings, together with the present results may provide genetic evidence to support epidemiological studies associating sleep disturbance with the development of diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although we did not perform any assessment of sleep patterns in our subjects, it is of interest that the rs1801260 polymorphism has previously been associated with sleep dysregulation in humans in many [31][32][33][34][35][36][37][38] but not all studies. 39 These findings, together with the present results may provide genetic evidence to support epidemiological studies associating sleep disturbance with the development of diabetes and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, suggestive evidence has recently been reported for the association of circadian gene variants including CLOCK, BMAL1, PER3 and TIMELESS with bipolar disorder. [31][32][33] Moreover, studies using pharmacogenomic animal models for bipolar disorder have revealed circadian genes as the candidate genes for mania and psychosis, which include BMAL1, GSK3b, CKId, CRY2 34 and DBP. 35 Despite the above-mentioned evidence implicating the circadian system in the pathophysiology of bipolar disorder, the functional and molecular basis of circadian anomalies in bipolar disorder has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Research in this area has noted that an evening chronotype is associated with rapid mood swings, 24 greater recurrence rates of affective episodes, 24 and an earlier age at illness onset. 24 Rhythmbased phenotyping may also prove to be of importance in defining treatment response, 21 associated variations in the functioning of molecular clocks, 25 genetic variations associated with the illness, [26][27][28][29][30] and heritable features of the disorder. 31 Longitudinal studies are needed to better understand the relationships between chronobiological disturbances and bipolar disorder and to establish potential chronobiologically based phenotypes for the illness.…”
Section: E2mentioning
confidence: 99%